A Philosophical Review Of Islamic Law of the Dynamics and Relevance of Idah for Career Women - Khotibul Umami; Zahrotul Habibah; Deny Marita Wijayanti; Rizky Ardiyanto (Hakamain: Journal of Sharia and Law Studies, 2025)
This paper examines the dynamics of Islamic law following the rise of the gender equality movement, such as women’s participation in the public sphere, and the dynamics of the sophisticated medical technology that impact the substance of idah. This paper aims to examine the relevance of idah and its implementation mechanism for career woman. This article was compiled using qualitative methods with an Islamic legal philosophy approach. Primary data sources were drawn from Islamic legal sources. Secondary data were obtained from accredited journal literature. The results indicate that the philosophical meaning of idah is divided into three aspects: ontological, epistemological, and axiological. From these three aspects, it was found that idah remains relevant for career woman because the ontological waiting period has implications for psychological recovery. Thus epistemologically, the obligation of idah aims to protect biological and sociological aspects. Therefore, idah, axiologically, means the command to maintain biological values, protect the psyche, and maintain sociological relationships. The findings in this paper explain that the implementation of idah for career women cannot shift the fundamental meaning but can adapt iyts instrumental value based on urgency.